Oleanane Saponins and Glycerogalactolipids from the Leaves of Guapira graciliflora - Severi, Juliana A. [UNESP]; Fertig, Orlando; Plitzko, Inken; Vilegas, Wagner [UNESP]; Hamburger, Matthias; Potterat, Olivier (Wiley-Blackwell, 2010)
Two new saponins, 3-O-[beta-xylopyranosyl-(1 --> 3)-beta-D-galactopyranosyl-(1 --> 3)-beta-glucuronopyranosyl]oleanolic acid 28-O-beta-D-glucopyranosyl ester (1) and the corresponding monodesmoside, 3-O-[beta-xylopyranosyl-(1 --> 3)-beta-D-galactopyranosyl-(1 --> 3)-beta-glucuronopyranosyl]oleanolic acid (2), have been isolated from the leaves of Guapira graciliflora (Nyctaginaceae), together with two further oleanane saponins, 3 and 4, daucosterol (5), and two known glycerogalactolipids, 6 and 7 The structures of the new compounds were established by extensive NMR and MS experiments, in conjunction with acid hydrolysis and sugar analysis. This is the first report on the phytochemistry of plants of the genus Guapira.